Cryogenic Operation of Silicon Power Devices - Singh, Ranbir; Baliga, B. Jayant (The Springer International Series in Engineering and Computer Science, Power Electronics and Power Systems, 1998)
The advent of low temperature superconductors in the early 1960's converted what had been a laboratory curiosity with very limited possibilities to a prac tical means of fabricating electrical components and devices with lossless con ductors. Using liquid helium as a coolant, the successful construction and operation of high field strength magnet systems, alternators, motors and trans mission lines was announced. These developments ushered in the era of what may be termed cryogenic power engineering and a decade later successful oper ating systems could be found such as the 5 T saddle magnet designed and built in the United States by the Argonne National Laboratory and installed on an experimental power generating facility at the High Temperature Institute in Moscow, Russia. The field of digital computers provided an incentive of a quite different kind to operate at cryogenic temperatures. In this case, the objective was to ob tain higher switching speeds than are possible at ambient temperatures with the critical issue being the operating characteristics of semiconductor switches under cryogenic conditions. By 1980, cryogenic electronics was established as another branch of electric engineering